The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0104-66321998000200004
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Condensation of Citral with Acetone on Basic Solid Catalysts

Abstract: The catalytic performance of solids with basic properties, such as CaO, MgO and hydrotalcites, was evaluated in the aldol condensation of citral and acetone, the first step in the synthesis of ionones from citral. The best results were obtained with CaO and hydrotalcite with high conversions (98%) and selectivities (close to 70% for the main product) observed for both of the catalyst. Such pseudoionone yields were greater than those reported in the literature for the homogeneous reaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In the present work, the citral purchased from Aldrich Co. (with 98 wt.% of citral isomers) substituted the Cuban lemongrass essential oil (91.3 wt.% of citral) used in the former studies [6,7]. The use of this more pure reactant decreased the formation of undesirable products, thus increasing both the citral conversion and the PSI selectivity as compared to those previously reported for the same catalyst on the same reaction conditions [7].…”
Section: Catalytic Testsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the present work, the citral purchased from Aldrich Co. (with 98 wt.% of citral isomers) substituted the Cuban lemongrass essential oil (91.3 wt.% of citral) used in the former studies [6,7]. The use of this more pure reactant decreased the formation of undesirable products, thus increasing both the citral conversion and the PSI selectivity as compared to those previously reported for the same catalyst on the same reaction conditions [7].…”
Section: Catalytic Testsmentioning
confidence: 87%
“…Noda et al [6] were the first to report the excellent performance of a Mg,Al-mixed oxide (Al/(Al + Mg) = 0.27) derived from hydrotalcite as a catalyst for this reaction under autogenous pressure, at 398 K with an acetone/citral molar ratio equal to 1 and a catalyst content of 10 wt.% (with respect to the total weight of reactants). After 4 h of reaction, a citral conversion of 98% was obtained with selectivity to pseudoionones close to 67%.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide variety of chemical compositions, they are very efficient catalysts in different reactions. Mg,Al-mixed oxides, for example, are active for base-catalyzed reactions such as aldol condensation of aldehydes and ketones, condensation of the carbonyl group with compounds presenting methylene activated groups (for example, Knoevenagel and Claisen-Schmidt reactions), alkene isomerization, alkylation of diketones and phenols, alkene epoxidation activated by hydrogen peroxide 4,[10][11][12][14][15][16][17][18][19][20][21] . HTLCs containing transition metals such as Ni, Co, Cu or Zn or noble metals such as Rh and Ru [22][23][24][25][26][27] have also been used as precursors for hydrogenation or redox catalysts for methanol synthesis from syngas 28 , removal of SOx and NOx from FCC effluents 29,30 and other redox reactions.…”
Section: -mentioning
confidence: 99%
“…Recently, Noda et al [20] studied the production of PS at 330 K using a calcined HT. These authors concluded that at lower temperatures, the condensation of citral with acetone requires stronger basic sites than for the self-condensation of acetone and preferably has to be executed at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%